Law Enforcement for Misuse of the Distribution of the Smart Indonesia Program (PIP) in One of the Cirebon City High Schools - Aprilia Maulani; Waluyadi Waluyadi; Gunadi Rasta (Jurnal Legisci, 2026)
Background. The Indonesia Pintar Program (PIP) is a government program that aims to reduce the dropout rate and improve access to education for students from underprivileged families. However, many mistakes still occur in its implementation, such as the misuse of aid funds. Purpose. By conducting a case study at a high school in Cirebon City, this study examines law enforcement efforts against the misuse of PIP funds. Method. The research method used is normative legal research with a literature study approach, through analysis of laws and regulations, legal literature, and secondary data in the form of reports and news related to cases. Results. The results of the study show that the misuse of PIP funds in this case meets the elements of corruption. The modus operandi involved cutting aid funds, controlling student accounts, and diverting funds for personal interests and certain parties. Law enforcement has been carried out through the processes of investigation, prosecution, and trial, with criminal penalties including imprisonment, fines, and payment of compensation to the defendants. Conclusion. Law enforcement against the misuse of PIP funds has been carried out in accordance with applicable law, but it is still necessary to strengthen supervision, transparency, and accountability in the management of education assistance funds to prevent a recurrence of similar practices.